Online condition monitoring system for DC-link capacitor in industrial power converters - Mohamed Halick Mohamed Sathik (2019)
This paper proposes an online condition monitoring system for aluminum electrolytic capacitors used as dc-link capacitors in industrial power converters. Electrolytic capacitors are one of the most fragile components of a power converter system because of their wear-out failures and short lifespan. Therefore, the use of condition monitoring systems for aluminum electrolytic capacitors allow preventive maintenance to be performed, thereby avoiding unexpected shutdown and downtime. The dominant wear-out mechanisms in aluminum electrolytic capacitors are characterized by the increase in equivalent series resistance. Hence, the condition monitoring system proposed in this paper is based on the online estimation of the capacitor's equivalent series resistance using the switching frequency components of the dc-link capacitor voltage and current. The equivalent series resistance estimation method is tested using the PSpice circuit simulator and is validated experimentally using a custom-made inverter. Finally, the equivalent series resistance estimation method is adapted for the condition monitoring of capacitors in industrial power converters and the proposed condition monitoring system is implemented in a commercial ac drive system to prove the applicability of the proposed method to industrial power converters.